Peran Kejaksaan Dalam Pencegahan Dan Penanganan Tindak Pidana Korupsi Dana Desa Di Wilayah Hukum Kejaksaan Tinggi Sumatera - Ismarandy Ismarandy; Alfi Syahrin; M Hamdan; Rosnidar Sembiring (Iuris Studia: Jurnal Kajian Hukum, 2021)
Law Number 6 of 2014 concerning villages is the legal basis for the distribution and management of village funds. In its development, village funds are prone to corrupt practices. The lack of understanding of the village apparatus and the absence of policy instruments that are the parameters of success are crucial obstacles in village development. Law enforcement based on the restorative, corrective and rehabilitative paradigm is an effort made by the North Sumatra High Court in handling the crime of corruption in village funds. In minimizing the occurrence of irregularities in the distribution and management of village funds in the North Sumatra Province, the formation of the P3TPK Task Force, TP4D, the AKUR Program (Ayo Kawal Uang Rakyat), and the